Securing interim payments in construction projects through a blockchain-based framework - Das, Moumita; Luo, Han; Cheng, Jack C.P. (Automation in construction, 2020)
Interim payment provisions in construction projects are susceptible to unfair practices. In construction project participants with varying financial capacities belonging to different organizations are bound by contractual relationships. Due to this type of project organizational structure, project participants do not completely trust each other which prevents the adoption of existing centralized automated frameworks for interim payment. Therefore, this paper presents a distributed blockchain-based framework that does not require to be trusted for automatically enforcing the terms and conditions related to interim payments and sharing payment records at project-level transparently and securely. A logic to automatically initiate, validate, and disburse interim payments according to general contract conditions for interim payments is formalized in this paper. A blockchain-based data model that enables selective-transparency in payment records is proposed. This data model facilitates the sharing of sensitive financial information privately between two contracting parties and non-sensitive payment-related information publicly among all project participants. The proposed blockchain-based framework is supported by a key management strategy to facilitate different security properties such as confidentiality and authenticity of data and users. Considering the non-technical nature of construction project participants, the proposed key management strategy is designed to dynamically generate cryptographic keys from publicly sharable parameters so that storage and management overheads are reduced. Security properties such as immutability, data confidentiality, user integrity, performance, and cost of deployment of the proposed blockchain framework are validated and recommendations for executing the proposed framework with a high level of security are discussed in this paper. •Automated and secure execution of interim payment via smart contracts is facilitated.•Data model for selectively-transparent recording of payments on blockchain is presented.•A blockchain-based key management strategy for data confidentiality in construction projects is presented.•Cost and security of the framework are evaluated and discussed.